An Airborne Lidar-Based 15-Year Study of Dune Reconstruction and Overwash Formation in a Microtidal and Fetch Limited Environment - Clara Armaroli; Riccardo Brunetta; Paolo Ciavola (Remote Sensing)
This paper examines the long-term morphological evolution of the Bevano River sand spit (Ravenna, Italy) after an artificial intervention carried out in 2006 that artificially relocated the river mouth to improve the hydraulic efficiency, preventing flooding and reconstructing a local dune system. Using multitemporal Lidar data (2004–2019), combined with orthophotos and a storm dataset, this study analysed shoreline changes and morphological variations, highlighting the role of overwash processes in sediment transfer from the dunes to back-barrier areas. Based on the analysis, a set of washover fans was identified that began to form after a storm event in 2008 and accreted until 2015. These fans, which later coalesced into terraces and were colonised by vegetation, became stable after 2015. Despite an initial low resilience, due to insufficient nourishment and slow vegetation development, the barrier system eventually stabilised, with dunes growing higher and forming a continuous dune crest. The study illustrates the role of surge levels, waves, and low initial elevation in triggering and shaping overwash processes.